A Complete Review of Design, Performance, and Future Developments of CPVT Systems - Calik, Keziban; Firat, Coskun (New Energy Exploitation and Application, 2025)
Concentrated Photovoltaic‑Thermal (CPVT) systems combine concentrated photovoltaics and thermal energy recovery. This lets them produce electricity and heat from sunlight at the same time. This paper looks at the latest progress in optical concentrators, thermal management methods, and spectral beam splitting techniques. These advances have boosted the system’s overall efficiency to between 60% and 80% under different operating conditions. Particular attention is given to Linear Fresnel Reflectors (LFRs), thermal‑fluid simulations, and the use of artificial intelligence (AI) to improve system design and performance. Modeling methods, such as computational fluid dynamics and ray tracing, are examined to connect theoretical expectations with actual experimental data. The discussion includes major obstacles, like the systems’ reliance on high direct normal irradiance (DNI) and their comparatively high initial expenses. Policy changes that could encourage broader use are suggested. Unlike earlier studies, this review incorporates research from 2024–2025 on AI‑driven controls, hybrid energy storage solutions, and strategies for functioning in areas with low DNI. A meta‑analysis is offered, showing how these changes can lower the levelized cost of electricity (LCoE) to between 0.08 and 0.15 per kilowatt‑hour. The article concludes by exploring potential future research areas, such as creating scalable hybrid systems that can support sustainable energy grids. These developments are aimed at assisting the transition toward energy infrastructures with lower carbon emissions.